Best practice of nurse managers in risk management - Veridiana Tavares Costa; Betina Horner Schlindwein Meirelles; Alacoque Lorenzini Erdmann (Universidade de São Paulo, 2013)
OBJECTIVE: to identify the actions, undertaken by nurse managers in a risk management program, considered as best practice. METHOD: a case study undertaken in a private hospital in the south of Brazil. A risk manager and nurse managers working in a risk management program participated in this study. The data was collected between May and September 2011 through analysis of documents, semi-structured interviews and non-participant observation. Based on the triangulation, the data was analyzed through practical measures. RESULTS: educational actions, the critical analysis of the context, and the multiple dimensions of the management were evidenced as best practice. CONCLUSIONS: the broadening of understanding regarding risk management best practice offers further support for nurse managers to achieve excellence in their actions and thus provide safe and quality care.